(3JJeg GdjJegs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3CeG HYO MeO Gddg GdPi habfG dZQS GdOQ GdjGbhJ ai GdcJH aEfi deG QCjJ cJGHi GdeYfhf jJjeg GdOgQ s
(3LRAGf ai eLdO hGMOs
(3QYfGhjfgG ecJhHgs
(3HGdPgH hGdMHQ HGgJ ZjQ hGVMs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs